1986
DOI: 10.1007/bf00981139
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of diclofenac sodium after intramuscular administration in combination with triamcinolone acetate

Abstract: Seventy-five mg diclofenac sodium were given intramuscularly to 15 subjects alone and in combination with 40 mg triamcinolone acetate. Plasma levels of diclofenac were measured and pharmacokinetic parameters were calculated. The results indicate no statistically significant differences for most of the parameters. The maximum plasma concentrations (Cpmax) was increased by about 20% in combination with the glucocorticoid, whereas terminal elimination rate did not change significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
2
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
1
5
2
1
Order By: Relevance
“…In the three trials described in the present paper, t max with test formulations was reached remarkably faster, even with the film coated tablets (Trial 2), as shown in Table 4. These t max values are shorter even than peak times obtained by other authors [11,12] after intramuscular administration of diclofenac sodium salt. According to these authors, the diclofenac peak was in fact reached 15 [11] and 25 min [12] after dosing.…”
Section: Discussioncontrasting
confidence: 57%
“…In the three trials described in the present paper, t max with test formulations was reached remarkably faster, even with the film coated tablets (Trial 2), as shown in Table 4. These t max values are shorter even than peak times obtained by other authors [11,12] after intramuscular administration of diclofenac sodium salt. According to these authors, the diclofenac peak was in fact reached 15 [11] and 25 min [12] after dosing.…”
Section: Discussioncontrasting
confidence: 57%
“…They speculated that the pharmacokinetic interaction, which is unique to diclofenac, was caused by the inhibition in the ®rst-pass metabolism of diclofenac by cyclosporin. On the other hand, Derendorf et al (1986) detected a slight increase (approximately 20%) in the C max of diclofenac after intramuscular administration of a combination of diclofenac and triamcinolone acetate. Figure 3 shows the mean ketoprofen plasma concentration±time pro®les after oral dosing of 1 mg kg À1 alone or when co-administered with AZT (1Á5 mg kg À1 , p.o.)…”
Section: Drugmentioning
confidence: 88%
“…However, it was concluded that the change was due to an increased absorption rate. [97] From the studies published so far, no final conclusion regarding the interaction between NSAIDs and steroids can be drawn; however, the interaction does not appear to have any clinical relevance. Moreover, although the interaction potential seems unimportant, one has to consider that concurrent administration of corticosteroids and NSAIDs in the elderly is a risk factor in itself for the development of upper gastrointestinal bleeding.…”
Section: 6 Steroid Hormonesmentioning
confidence: 93%